THE ROLE OF IMPORTED INPUTS AND FDI ON ECONOMIC GROWTH: EVIDENCE FROM EMERGING AND ADVANCED ECONOMIES - Maria Teresa Fernández Núñez; María Maesso Corral; Miguel Angel Márquez Paniagua (Revista de Economía Mundial, 2017)
The role of imported inputs (capital and intermediate goods) and foreign direct investment [FDI] on economic growth as a mechanism of international technology transfer has been highlighted by different growth models. However, empirical evidence regarding the concurrent impact of both imported inputs and FDI on economic growth is still scarce. The main aim of the paper is to give empirical evidence about the effects of these variables  as channels of international technology diffusion. In the same framework, this study captures the different responses in economic growth when considering two different groups of countries separately, emerging and advanced. Our findings reveal different responses in economic growth between advanced and emerging countries. Some important economic political recommendations can be derived from the empirical results.